THE IMPACT OF PEDAGOGICAL SUPPORT PROGRAM ON COPING STRATEGIES, ACADEMIC ACHIEVEMENT AND STRESS LEVEL IN ADOLESCENCE - Maslova, Jūlija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article analyses development of coping strategies and coping resources using in adolescence. Adolescents are often not able to cope with stressful situations because their coping strategies still forming, that leads to academic performance reduction. Therefore, a pedagogical support program for developing coping strategies in adolescents is crucial, and it was elaborated and approved as a formative experiment method. Results revealed that after the implementation of pedagogical support program in the experimental group there were identified effective coping strategies. Also, it was observed that the academic achievement level increased and the stress level decreased in the experimental group.